Differentiation of human bone marrow-derived mesenchymal stem cells into functional pancreatic beta cells - Ayla Eker Sariboyaci; Onur Uysal; Sibel Gunes (Medicine Science, 2021)
Two challenges must be overcome to achieve successful therapeutic strategies for type 1 diabetes mellitus (T1DM), as stated by the International Juvenile Diabetes Research Foundation. The first one is the regeneration of the destructed beta-cells and the presence of cell resources that will provide it, the second one is the usage of immunosuppressive drugs throughout life after the transplantation. To date, three different strategies have been developed, aiming at beta cell replacement; pancreatic transplantation, islet transplantation, and cellular therapy (islet-neogenesis). Stem cell-based therapy can be achieved by transplanting cells into a target organ to restore the functions of that organ. Experimental and clinical studies have provided promising results of the application of mesenchymal stem cells (MSCs) in diabetes therapy. MSCs have the potential to be applied in many clinical fields such as autoimmune and hereditary diseases treatment, transplantation, and regenerative medicine because of their immunoregulatory properties. Although there are many studies focused on β-cell replacement, it has been observed that beta cells have not been obtained yet at the desired morphological and functional level. This study aimed to differentiate hBM-MSCs in-vitro, into both morphologically and functionally pancreatic progenitor cells. For this purpose, hBM-MSCs were differentiated into beta-cells by a differentiation method in which culture conditions were modified. The differentiation efficiency of the obtained cells was analyzed. In our results, it was determined that the cells obtained when hBM-MSCs were differentiated with inductors added to the medium, were expressing beta-cell-specific markers and had morphological and functional features of the beta cells. Effective differentiation methods, including using different types of MSCs obtained from different tissues should be developed as the source of cell-based therapies for the treatment of type 1 diabetes. [Med-Science 2021; 10(3.000): 951-8]